0171 Do family and individual characteristics affect the experience of physical and psychosocial work environment in Danish 20/21 year olds?. (23rd June 2014) - Nohr Winding, Trine; Labriola, Merete; Aagaard Nohr, Ellen; Hviid Andersen, Johan
Abstract : Objectives: To describe the work environment of Danish 20/21 year olds and to investigate the influence of family socioeconomic background or individual characteristics at age 14/15 on later experience of physical and psychosocial work environment. Method: The study population consisted of 695 young people with primary work affiliation at age 20/21 who were derived from a prospective youth cohort. Outcome information from the questionnaire in 2010 consisted of six questions about psychosocial work environment and two questions about physical work environment. Exposure information about school performance, vulnerability, health and parental socioeconomic status was derived from the questionnaire in 2004 and from registers. Results: Overall, the psychosocial work environment of the young people was good but they experienced more repetitive movements and hard physical work than older workers. Individual as well as family factors in late childhood all together only had limited impact on how young people report later work environment. Low self-esteem at age 14/15 was associated with experiencing high demands, low trust and low fairness at work. In girls low self-esteem and low sense of meaningfulness were associated with experiencing low influence at work. Low parental socioeconomic status was associated with poor physical work environment. Conclusions: This study showed a social gradient in experiencing poor physical work environment at age 20/21. The psychosocial work environment in young people was on average good, but it seems that vulnerable young people need special intention in order to prevent them from being selected into psychosocial demanding job functions later in life.